Construção de valores em uma escola agroecológica no sul de Minas Gerais: desafios do desenvolvimento sustentável - Ferreira, Michael (2016)
This work is the result of a case study carried out in the Agroecological School of Esperança Ranch. The contributions given by the presence of agroecological principles of a Political Pedagogical Project in the School were investigated having in mind the devolopment of values by the students. Reflections upon this builing of values were related to the discussion of an axiological concern towards the foundation of an intersubjectively valid ethics in the core of the discussion which revolves around the concept of Sustainable Development. The objectives were, therefore, the identification of the agroecological principles present in the Pedagogical Political Project of the school, the identification of the relationship between these principles and values developed by the students and the association of these values to a characterization of what we call the subject of the transition to a more sustainable society. To this end, interviews were conducted with the school community, as well as observations and documentary analysis of the Pedagogical Political Project. The collected data were the basis for the raising of themes and discussions towards the research objectives. The identified agroecological principles were holism, synergy, diversity, appreciation of local knowledge, horizontal communication, sustainability and ethics. The values perceived in the school and community were the care, respect, harmonious relationship with nature and the other beings, communication, patience, conscious consumption, healthy eating, preservation, cooperation and love. Caring, as axiological category, and the reframing of the verb 'to use' is presented as essential in the proposed debate. The resonances of these values, scored as essentially human and distorted by social-historical evolution, reach the roots of the social and environmental issue.